A relação clínica e o processo de comunicação e informação na formação médica: resgate e proposta - Gularte, Natiele Dutra Gomes (2018)
The Physician-Patient Relationship, currently better known as Clinical Relation (CR), involves the doctor's contact with the patient, family members, health team and is a fundamental subject to be discussed during medical students training. However, in the midst of the technical study of diseases, diagnoses and treatments, there is little room in the medical curriculum for discussion and practice of such subjective topics. Given the wide range of active methodologies available for CR teaching and the importance of it in medical practice, it is important to provide students of the medical school with opportunities to deepen their knowledge in this area. The project consisted of six workshops offered to 33 students of the medical course, from the fourth semester, previously selected. At each meeting, specific subjects related to CR themes were discussed, such as: communication skills, difficult news communication, palliative care, coping with mourning and death. This qualitative-quantitative study evaluated, through the quantitative research, the students' previous conceptions about the aspects of the clinical relation through the application of a structured self-administered questionnaire. Qualitative research was carried out through two focus groups where students' perceptions about the project and the importance of CR in graduation and professional practice were discussed. After analysis of content, four main categories were identified: learning and teaching active methodologies (work in small groups, use of art, music and cinema, insertion in multidisciplinary conviviality); influence of communication (bad news and living accounts of patients who have received difficult news); death and mourning - words not spoken; values as a form of rescue and empathy as the guiding thread of CR. In our experience, small-group discussions, psychological support, and the various workshop methodologies have demonstrated a positive effect in mobilizing feelings and awakening empathy. Thus, based on the research project, the intention to retake the importance of RC provides spaces for discussion, theoretical and practical references that sensitize and favor the rescue of one of the main medical actions: interpersonal communication.